Jehovah’s witnesses and bioethics, right to treatment and religious freedom (BioLaw Journal - Rivista di BioDiritto, 2023)
The Jehovah’s Witnesses’ refusal of blood transfusions has traversed legal and scientific culture for several decades, leaving an indelible mark. The analysis starts from the religious motivations for such a choice, and examines the propulsive stimulus offered to the judiciary to cover the regulatory gap with its decisions, to the legislature to pass the law on informed consent, and to physicians driven to develop new techniques and to apply bloodless medicine more and more widely. The article focuses on the particular use of advance directives in a pro-life sense, the important results achieved and the difficulties that still exist in the application of the patient’s right.
Keywords: Religious freedom; Jehovah’s Witnesses; blood transfusion; informed consent; advanced directives